Analysis of a FliM-FliN flagellar switch fusion mutant of Salmonella typhimurium. - Kihara, M (1996)
In the course of an analysis of the three genes encoding the flagellar motor switch, we isolated a paralyzed mutant whose defect proved to be a 4-bp deletion of the ribosome binding sequence of the fliN switch gene (V. M. Irikura, M. Kihara, S. Yamaguchi, H. Sockett, and R. M. Macnab, J. Bacteriol. 175:802-810,1993). This sequence lies just before the 3' end of the coding sequence of the upstream fliM switch gene, in the same operon. This mutant readily gave rise to pseudorevertants which, though much less motile than the wild type, did exhibit significant swarming. One such pseudorevertant was found to contain a compensating frameshift such that the fliM and fliN genes were placed in frame, coding for an essentially complete FliM-FliN protein fusion. Minicell analysis demonstrated that, as expected, the parental mutant synthesized an essentially full-length FliM protein but no detectable FliN. The pseudorevertant, in contrast, synthesized a protein with the predicted size for the FliM-FliN fusion protein and no detectable FliM or FliN. Immunoblotting of minicells with antibodies against FliM and FliN confirmed the identities of these various proteins. Immunoblotting of book-basal-body complexes from the wild-type strain gave a strong signal for the three switch proteins FliG, FliM, and FliN. Complexes from the FliM-FliN fusion mutant gave a strong signal for FliG but no signal for either FIiM or FliN; a moderately strong signal for the FliM-FliN fusion protein was seen with the anti-FliM antibody, and a weaker signal was seen with the anti-FliN antibody. The cytoplasmic C ring of the structure, which is seen consistently in electron microscopy of wild-type complexes and which is known to contain the FliM and FliN proteins, was much more labile in the FliM-FliN fusion mutant, giving a fragmented and variable appearance or being completely absent. Complementation data indicated that wild-type FliM had a mild dominant negative effect over the fusion protein, that wild-type FliN and the fusion protein work much better than the fusion protein alone, and that wild-type FliM and FliN together have no major positive or negative effect on the function of the fusion protein. We interpret these data to mean that the FliM-FliN fusion protein incorporates into structure but less stably than do the FliM and FliN proteins separately, that wild-type FliM tends to displace the fusion protein, and that wild-type FliN can supplement the FliN domain of the fusion protein without displacing the FliM domain. The data support, but do not prove, a model in which FliM and FliN in the wild-type switch complex are stationary with respect to each other.